ANALISIS TEORI DAN EKSPERIMENTAL PENGUMPUL SURYA DUA-PASS DENGAN MEDIA BERPORI - Supranto Supranto (Teknoin, 2006)
The double-pass solar collector with porous media in the lower channel provides a higher outlet temperature compared to conventional single-pass collector. Therefore, the thermal efficiency of the solar collector is higher. The solar collector can be used for wide variety of applications such as solar industrial process heat and solar drying of agricultural products. A theoretical model has been developed for the double-pass solar collector. An experimental setup has been designed and constructed. Comparison of the theoretical and the experimental results have been conducted. Such comparisons include the outlets temperatures and thermal efficiencies of the solar collector for various design and operating conditions. Close agreement has been obtained between the theoretical and experimental results.Keywords: double-pass solar collector, porous media, theoretical, experimental, efficiency.